Design of a phase III, double-blind, randomised, placebo-controlled trial of BI 1015550 in patients with idiopathic pulmonary fibrosis (FIBRONEER-IPF) - Richeldi, Luca; Azuma, Arata; Cottin, Vincent; Kreuter, Michael; Maher, Toby M.; Martinez, Fernando J.; Oldham, Justin M.; Valenzuela, Claudia; Gordat, Maud; Liu, Yi; Stowasser, Susanne; Zoz, Donald F.; et al. (BMJ Open Respiratory Research, 2023)
There is an unmet need for new treatments for idiopathic pulmonary fibrosis (IPF). The oral preferential phosphodiesterase 4B inhibitor, BI 1015550, prevented a decline in forced vital capacity (FVC) in a phase II study in patients with IPF. This study design describes the subsequent pivotal phase III study of BI 1015550 in patients with IPF (FIBRONEER-IPF).
Gesehen am 28.11.2023